(untitled) (World of finance, 2023)
Introduction. The legal framework for tax administration is one of the important components of the harmonization of Ukrainian legislation with EU standards. The area of taxation of energy products is especially relevant today, because with the Russian invasion in Ukraine, there is a total deficit and an increase in prices for energy products. Instead, the taxation of such goods is the least harmonized with EU standards among of all excise goods. The unification of excise tax rates on energy products with the requirements of the relevant EU directive can further provoke the price growth, which is extremely undesirable in the current situation. The purpose of the article is to generalize scientific and legal approaches to the characteristics of excise taxation of energy products, to outline problematic aspects of the harmonization of the relevant directive in this area, to develop proposals for improving excise taxation of energy products in Ukraine. Results. The main provisions of Council Directive 2003/96/EC on excise taxation of energy products are analyzed. It has been established that the norms of the Tax Code of Ukraine do not comply with the provisions of this directive in terms of: the list and structure of energy products, which are the subject to excise tax; the amount of tax rates; provision of tax preferences. Probable directions for reforming the EU legislation on excise taxation of energy products are outlined. Monitoring of legislative activities on taxation of energy products in Ukraine was carried out. Conclusions. As a result of the research, the conclusion is substantiated that at the current stage, the tax policy in the field of excise taxation of energy products, focused on the socio-economic realities of Ukraine, will be more justified than on the priorities of harmonization to EU standards. However, in order for Ukraine’s European integration progress not to slow down due to the lack of reforms in terms of harmonization of the studied area, it is necessary to hold a number of consultations with EU institutions regarding the postponement of key issues of taxation of energy products.